Group‐AI Collaboration Enhances Creativity Performance: The Roles of Perspective‐Taking and AI Utilisation Strategies. - Zhou, Zhihao; Xiao, Letao; Wang, Jiayi; Tong, Shuai; Zhang, Wenyu; Hao, Ning (Journal of Computer Assisted Learning, 2026)
Background: The rise of generative artificial intelligence (AI) in educational research has prompted growing interest in how such tools might support collaborative knowledge construction and creative thinking. While most studies focus on individual‐AI interaction, less is known about group‐level cognitive and interactional processes when AI is integrated into shared problem‐solving settings. Objectives: This study investigates how group collaboration with AI supports creativity‐relevant processes in collaborative learning contexts and explores the psychological mechanisms that mediate this effect. Methods: Using a within‐subject experimental design, 96 university students engaged in a scientific divergent application task under three collaboration modes: group‐AI collaboration, individual‐AI collaboration and human‐only group collaboration. The study adopted a mixed‐method approach, combining behavioural coding of perspective‐taking and AI utilisation strategies with statistical modelling to examine mediation effects. Tasks were designed to simulate open‐ended learning scenarios that emphasise ideation, problem‐solving and conceptual integration—core components of collaborative learning. Results and Conclusions: Group‐AI collaboration led to the most creative outputs in terms of usefulness, originality and quality. This effect was mediated by two key mechanisms: strategic use of AI as a generative and exploratory resource and selective, high‐quality integration of both peer and AI‐generated ideas. While these findings stem from a controlled setting, they offer initial evidence that AI‐supported group work may enrich collaborative ideation processes and hold promise for future instructional design and group‐based learning practices. Summary: What is currently known about this topic? ○AI can enhance individual creativity in open‐ended learning tasks.○Most research focuses on individual‐AI interaction, not group‐AI collaboration.○Group creativity depends on cognitive diversity and mutual perspective taking.○Effective AI use requires strategic engagement, not passive reliance.What does this paper add? ○Group‐AI collaboration outperforms both individual‐AI and human‐only groups.○AI supports perspective taking by enabling selective idea elaboration.○Group‐AI users adopt more high‐quality AI ideas via strategic engagement.○AI reshapes team cognition and improves idea evaluation across task stages.Implications for practice/or policy. ○Educators should embed AI into group‐based learning, not just individual tasks.○Instructional design should promote critical and stage‐specific AI use.○Training in selective idea adoption may boost team innovation outcomes.○Policies should encourage collaborative AI literacy in education systems.